Work disability, work, and justification bias in Europe and the U.S. - Arie Kapteyn; James P. Smith; Arthur van Soest (Institute for the Study of Labor (IZA), 2009)
To analyze the effect of health on work, many studies use a simple self-assessed health measure based upon a question such as do you have an impairment or health problem limiting the kind or amount of work you can do? A possible drawback of such a measure is the possibility that different groups of respondents may use different response scales. This is commonly referred to as differential item functioning (DIF). A specific form of DIF is justification bias: to justify the fact that they don't work, non-working respondents may classify a given health problem as a more serious work limitation than working respondents. In this paper we use anchoring vignettes to identify justification bias and other forms of DIF across countries and socio-economic groups among older workers in the U.S. and Europe. Generally, we find differences in response scales across countries, partly related to social insurance generosity and employment protection. Furthermore, we find significant evidence of justification bias in the U.S. but not in Europe, suggesting differences in social norms concerning work.
Keywords: J28; I12; C81; 330; Work limiting disability; vignettes; reporting bias; Arbeitswelt; Anforderungsprofil; Gesundheit; Stress; Bewertung; Persönlichkeitspsychologie; Soziale Sicherung; Vergleich; USA; EU-Staaten